Risk factors for stroke after total aortic arch replacement using the frozen elephant trunk technique. (29th January 2022) - Berger, Tim; Kreibich, Maximilian; Mueller, Felix; Breurer-Kellner, Lara; Rylski, Bartosz; Kondov, Stoyan; Schröfel, Holger; Pingpoh, Clarence; Beyersdorf, Friedhelm; Siepe, Matthias; Czerny, Martin
Abstract: OBJECTIVES: This study aimed to analyse risk factors for postoperative stroke, evaluate the underlying mechanisms and report on outcomes of patients suffering a postoperative stroke after total aortic arch replacement using the frozen elephant trunk technique. METHODS: Two-hundred and fifty patients underwent total aortic arch replacement via the frozen elephant trunk technique between March 2013 and November 2020 for acute and chronic aortic pathologies. Postoperative strokes were evaluated interdisciplinarily by a cardiac surgeon, neurologist and radiologist, and subclassified to each's cerebral territory. We conducted a logistic regression analysis to identify any predictors for postoperative stroke. RESULTS: Overall in-hospital was mortality 10% (25 patients, 11 with a stroke). A symptomatic postoperative stroke occurred in 42 (16.8%) of our cohort. Eight thereof were non-disabling (3.3%), whereas 34 (13.6%) were disabling strokes. The most frequently affected region was the arteria cerebri media. Embolism was the primary underlying mechanism ( n = 31; 73.8%). Mortality in patients with postoperative stroke was 26.2%. Logistic regression analysis revealed age over 75 (odds ratio = 3.25; 95% confidence interval 1.20–8.82; P = 0.021), a bovine arch (odds ratio = 4.96; 95% confidence interval 1.28–19.28; P = 0.021) and an acute preoperative neurological deficit (odds ratio = 19.82; 95% confidence interval 1.09–360.84; P = 0.044) as predictors for postoperative stroke. CONCLUSIONS: Stroke after total aortic arch replacement using the frozen elephant trunk technique remains problematic, and most lesions are of embolic origin. Refined organ protection strategies, and sophisticated monitoring are mandatory to reduce the incidence of postoperative stroke, particularly in older patients presenting an acute preoperative neurological deficit or bovine arch. Abstract : Total aortic arch replacement (TAR) using the frozen elephant trunk (FET) technique was introduced in 2003 [1], and it has since been refined: for one, off-the-shelf hybrid prostheses became available in different modifications and lengths, and secondly, surgical techniques improved as zone 2 distal anastomosis simplified implantation and lowered the incidence of postoperative spinal cord injuries [2, 3].